Long-term bisphenol S exposure aggravates non-alcoholic fatty liver by regulating lipid metabolism and inducing endoplasmic reticulum stress response with activation of unfolded protein response in male zebrafish. (August 2020) - Qin, Jingyu; Ru, Shaoguo; Wang, Weiwei; Hao, Liping; Ru, Yiran; Wang, Jun; Zhang, Xiaona
Abstract: Environmental chemical exposures have been implicated as risk factors for the development of non-alcoholic fatty liver (NAFLD). Bisphenol S (BPS), widely used in multitudinous consumer products, could disrupt lipid metabolism in the liver. This study aimed at examining the hypothesis that long-term exposure to BPS promotes the development of liver fibrosis and inflammation by means of the application of a semi-static exposure experiment that exposed zebrafish to 1, 10, and 100 μg/L BPS from 3 h post fertilization to 120 day post fertilization. Results showed that the 120-d BPS exposure elevated plasma aspartate aminotransferase and alanine aminotransferase activities, increased triacylglycerol (TAG) and total cholesterol levels in male liver, and even induced hepatic apoptosis and fibrosis. Hepatic lipid accumulation observed in the 30-d BPS-exposed zebrafish was recovered after a 90-d depuration phase, thereby indicating that long-term BPS exposure promotes the progression of simple steatosis to non-alcoholic steatohepatitis. Furthermore, BPS exposure for 120-d promoted the synthesis of TAG and lipotoxic free fatty acids by elevating the transcription of srebp1, acc, fasn, and elovl6, induced endoplasmic reticulum (ER) stress with increasing expression levels of unfolded protein response (UPR) genes ( perk, hsp5, atf4a, and ddit3 ), and then stimulated the expression of two key autophagy genes ( atg3 and lc3 ) and inflammatory genes ( il1b and tnfα ). It is indicated that BPS can induce the development of steatohepatitis via the activation of the PERK-ATF4 a pathway of the UPR. Data gathered suggest that environmental pollutants-induced ER stress with the activation of UPR can potentially trigger the NAFLD development in males. Overall, our study provided new sights into understanding of the adverse health effects of metabolism disrupting chemicals. Graphical abstract: Image 1 Highlights: Long-term BPS exposure promoted the progression of steatosis to NASH in male liver. BPS increased synthesis of hepatic TAG and lipotoxic free fatty acids. BPS induced NASH development via activation of the PERK pathway of the UPR. Abstract : Our study provides the first evidence that chronic BPS exposure promotes non-alcoholic fatty liver progression in male zebrafish via activation of unfolded protein response.